Analysis of the climate characteristics and influence system of thunderstorms in Fuzhou in recent 59 years - Jingguang ZHENG; Xiaoqin CAI (暴雨灾害, 2019)
Based on thunderstorm data from 11 meteorological observation stations in Fuzhou and NCEP reanalysis data during the period of 1960-2018, the temporal and spatial distribution characteristics and variation trend of thunderstorms are analyzed by using linear trend, Mann-Kendall test and wavelet analysis. The relationship between thunderstorm and meteorological elements, thunderstorm weather condition and main influential systems are also analyzed. The results show that the spatial distribution of thunderstorms in Fuzhou is spatially uneven, with more thunderstorms in the east than in the west and more thunderstorms in the south than in the north. There are 70.5 days of regional thunderstorms annually, and the thunderstorms days was gradually decreasing in the past 59 years, with an average decreasing rate of -4.46 d·(10 a)-1 Thunderstorms mainly occur in spring and summer, with thunderstorm days in the two seasons accounting for 86.6% of the total thunderstorm days in the whole year. Most of thunderstorms occur in April during spring and in August during summer. The occurrence time of thunderstorms has an obvious diurnal variation. The thunderstorms mainly occur from 13:00 to 20:00. The thunderstorm days in Fuzhou changed abruptly in 1987, with a short period of 3-6 years, a decadal variation of 13-15 years and a low-frequency oscillation of about 21 years. The weather condition of thunderstorms in Fuzhou mainly includes frontal type, upper trough (shear line), subtropical high edge, easterly wave and inverted trough type.